تقويم التفاعل الاجتماعي بين أطفال الروضة في بغداد - الشبلاوي، شهد عباس عبيد حسين; ردام، كلثوم عبد عون (جامعة بغداد - مركز البحوث التربوية والنفسية, 2024)
يهدف البحث التعرف على: 1. التعرف على مستوى التفاعل الاجتماعي لطفل الروضة. 2. دلالة الفرق في التفاعل الاجتماعي وفق متغير الجنس (ذكور، إناث). 3. دلالة الفرق في التفاعل الاجتماعي وفق متغير نوع الروضة (حكومي، أهلي). 4. دلالة الفرق في التفاعل الاجتماعي وفق متغير مهنة الأم (عاملة، غير عاملة). ولتحقيق الأهداف قامت الباحثة بتبني مقياس التفاعلات الاجتماعية للأطفال للباحث عادل عبد الله محمد وطبق المقياس على عينة عشوائية من أمهات الأطفال الملتحقين برياض الأطفال الحكومية والأهلية في محافظة بغداد بمديرياتها الست وبلغ عدد العينة (350) أما وتم التحقق من الصدق للمقياس ظاهريا وذلك بعد عرضه على مجموعة من المختصين والخبراء في رياض الأطفال والعلوم النفسية والتربوية والقياس والتقويم واستخرجت الباحثة الخصائص السايكومترية للمقياس عن طريق مؤشرات الصدق والثبات وتم استخدام البرنامج الإحصائي (SPSS) في استخلاص المعالجات الإحصائية (تحليل التباين، الاختبار التائي، الانحراف المعياري، الوسط الحسابي، معادلة ألفا كرونباخ) توصلت الباحثة إلى النتائج الآتية:- 1. إن عينة البحث لديهم تفاعل اجتماعي بمستوى مرتفع. 2. هناك فرق في التفاعل الاجتماعي وفق متغيري الجنس (ذكور، إناث) ولصالح الذكور. 3. هناك فرق في التفاعل الاجتماعي وفق متغيري نوع الروضة (حكومي، أهلي) ولصالح الحكومي. 4. هناك فرق في التفاعل الاجتماعي وفق متغيري مهنة الأم (عاملة، غير عاملة) ولصالح الأم غير عاملة. The research aims to identify the social interaction of kindergarten children, the significance differences in social interaction between boys and girls, the significance differences of kindergarten type in social interaction (governmental, private), and the significance differences of the mother's profession in social interaction (housewife, working). To achieve these objectives, the researcher adopted Adel Abdullah Muhammad's scale for children's social interactions, the scale was used for a random sample of mothers whose children were enrolled in governmental and private kindergartens across the six districts of Baghdad. The sample size consisted of 350 mothers. The researcher confirmed the reliability and validity of the scale by presenting it to a group of experts and specialists in kindergarten, psychological and educational sciences, measurement, and evaluation. Psychometric characteristics of the scale were derived using indicators of validity and reliability, and the statistical program SPSS was employed to perform statistical analyses such as analysis of variance, t-test, standard deviation, mean, and Cronbach's alpha equation. The results revealed that the research sample has a high level of social interaction. There were significant differences in social interaction between boys and girls in favor of boys. There were significant differences in social interaction based on the type of kindergarten, where governmental kindergartens showed more favorable outcomes. There were significant differences in social interaction based on the mother's profession; housewives had more favorable outcomes.
Keywords: المهارات الاجتماعية -- العلاقات الاجتماعية -- رياض الأطفال -- السلوك الإنساني -- القيم الأخلاقية